Cultural Biases in Equity Analysis - PURSIAINEN, VESA (Journal of Finance, 2022)
ABSTRACT A more positive cultural trust bias by an equity analyst's country of origin toward a firm's headquarter country is associated with significantly more positive stock recommendations. The cultural bias effect is stronger for eponymous firms whose names mention their home country and varies over time, increasing with negative sentiment. I find evidence of a negative North‐South bias during the European debt crisis and United Kingdom‐Europe divergence amid Brexit. Share price reactions to recommendations by more biased analysts are weaker, and more biased recommendations are worse predictors of monthly stock returns. More positively biased analysts also assign higher target prices.